2014
DOI: 10.1080/19338244.2013.771248
|View full text |Cite
|
Sign up to set email alerts
|

Noise Levels in Fitness Classes Are Still Too High: Evidence From 1997–1998 and 2009–2011

Abstract: Fitness instructors routinely use high music volumes that may be harmful to hearing. This study assessed noise levels during 35 low-intensity and 65 high-intensity fitness classes in 1997-1998 and 2009-2011. Questionnaires examined instructors' and clients' preferred music volumes and whether they found loud music "stressful" or "motivating." Noise levels in 1997-1998 and 2009-2011 were similar, frequently exceeding 90 dB(A). Although noise levels in low-intensity classes dropped from 88.9 to 85.6 dB(A), they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
(18 reference statements)
2
15
0
5
Order By: Relevance
“…7 Finally, Beach and Nie studied Australian fitness classes and found that from 2009 to 2011, among several high-intensity exercise classes, cycle or spin classes were the loudest, with an average sound level of 94.0 dBA. 6 Our findings support this previous work and additionally find that U.S.-based spin classes may actually expose participants to higher sound levels (average 5 100.8 6 1.8 dBA) than previously recorded. This report differs from previous studies in that it is among the first of its kind to use accessible smartphone-based software to assess noise exposure risk from the consumers' perspective.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7 Finally, Beach and Nie studied Australian fitness classes and found that from 2009 to 2011, among several high-intensity exercise classes, cycle or spin classes were the loudest, with an average sound level of 94.0 dBA. 6 Our findings support this previous work and additionally find that U.S.-based spin classes may actually expose participants to higher sound levels (average 5 100.8 6 1.8 dBA) than previously recorded. This report differs from previous studies in that it is among the first of its kind to use accessible smartphone-based software to assess noise exposure risk from the consumers' perspective.…”
Section: Discussionsupporting
confidence: 91%
“…In a United Kingdom–based study of aerobics classes, Nassar reported sound levels of 89 to 96 dBA, and all subjects had significantly elevated hearing thresholds after classes . Finally, Beach and Nie studied Australian fitness classes and found that from 2009 to 2011, among several high‐intensity exercise classes, cycle or spin classes were the loudest, with an average sound level of 94.0 dBA . Our findings support this previous work and additionally find that U.S.‐based spin classes may actually expose participants to higher sound levels (average = 100.8 ± 1.8 dBA) than previously recorded.…”
Section: Discussionsupporting
confidence: 86%
“…Critically however, the use of auditory cues in training or sporting environments needs to take careful consideration of sound volume given that it is well established that high exposure to loud noise can result in cumulative (and irreversible) hearing loss. Indeed, such concerns have arisen in recent media (Hallett, 2015) which highlights findings from the Australian National Acoustic Laboratories which show that most gyms are already too loud (and getting louder), exceeding safe noise levels (Beach and Nie, 2014).…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…All 14 subjects in the exposure group sustained various levels of TTS. Additional studies found noise levels during aerobics classes of 105 dBA (Center for Hearing and Communication, n.d.), 87.1 dBA (Torre & Howell, 2008), 93.1 dBA (Beach & Nie, 2013) and 95.86 dBA in a Brazilian indoor bike class (Palma, Mattos, Almeida, & Oliveira, 2009).…”
Section: Aerobics Classes and Noise (Music)mentioning
confidence: 89%